AIR (AKSI INOVATIF RAKYAT): PROGRAM FILTER AIR BERBASIS TEKNOLOGI SEDERHANA YANG DITERAPKAN DI KELURAHAN SASAKE LOMBOK TENGAH - Sulistiyono, Heri; Wibowo, Nazwa Rizka; Fajira, Era; Avriliani, Salsabila; Arini, Nyoman Ayu; Fauzia, Isna; Akbar, Andi Rahman; Firdaus, Muhamad Arsya Maulana; Khaliilulrahman, Khaliilulrahman; Solihin, Muhammad Anhar; Budiarti, Wiwin (Jurnal Wicara, 2025)
The availability of clean water is a vital necessity for the community; however, in Sasake Village, problems related to water quality are still found, particularly turbidity and high levels of metals such as iron. This condition affects health and the daily use of water. To address this issue, the KKN PMD students of Universitas Mataram 2025 implemented a simple water filter program using locally available and environmentally friendly materials. The aim of this activity was to improve community water quality through the application of a simple filter that is easy to build and independently applied. The method included preliminary observation of water sources, community training in making simple water filters, and laboratory testing to evaluate the effectiveness of the filtering process. The results showed that the simple water filter significantly reduced water turbidity, lowered iron content, and improved the physical quality of water, making it more suitable for consumption and daily use. Based on laboratory analysis, water quality after filtration increased and met basic feasibility standards. In addition, the community assessed that the filter was easy to use, cost-efficient, and highly beneficial in everyday life.